2015
DOI: 10.1167/15.10.16
|View full text |Cite
|
Sign up to set email alerts
|

The effect of normal aging and age-related macular degeneration on perceptual learning

Abstract: We investigated whether perceptual learning could be used to improve peripheral word identification speed. The relationship between the magnitude of learning and age was established in normal participants to determine whether perceptual learning effects are age invariant. We then investigated whether training could lead to improvements in patients with age-related macular degeneration (AMD). Twenty-eight participants with normal vision and five participants with AMD trained on a word identification task. They … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 81 publications
0
23
1
2
Order By: Relevance
“…For example, reading speed can improve significantly with practice in patients with advanced macular degeneration (Chung 2011, Astle et al 2015, Maniglia et al 2016). However these improvements seem to be mainly mediated by a reduced susceptibility to crowding rather than an improvement in low-level acuity (Chung 2013, He et al 2013).…”
Section: Perceptual Learningmentioning
confidence: 99%
“…For example, reading speed can improve significantly with practice in patients with advanced macular degeneration (Chung 2011, Astle et al 2015, Maniglia et al 2016). However these improvements seem to be mainly mediated by a reduced susceptibility to crowding rather than an improvement in low-level acuity (Chung 2013, He et al 2013).…”
Section: Perceptual Learningmentioning
confidence: 99%
“…Recent studies have succeeded in explaining some of the interindividual variability in the magnitude of learning effects. Factors that have been identified to explain the magnitude of visual perceptual learning include baseline performance (poor initial performers tend to show larger improvements, typically explaining 40% to 60% of the outcome variance), [8][9][10][11][12] number of training sessions, 11,13 age 14 (but note that there are also studies that found no effect of age [15][16][17] ), motivation and intelligence, 18 performance feedback, [19][20][21] the accuracy of performance during training, 22 heart-rate variability, 23 and reactivity of dopaminergic and cholinergic neuromodulatory systems. 24,25 The goal of the present study was to evaluate the contribution of physiological factors, such as baseline performance, age, and clinical diagnosis, and a psychological factor, the perceived pleasantness of the training (training joy).…”
mentioning
confidence: 99%
“…The latter were however able to complete less blocks because of fatigue. In Astle et al (2015), AMD patients were not trained in their PRL but rather at a fixed eccentricity (10°) and “asked to fixate the center of the fixation cross so that the end of the limbs appeared to extend equal distances into the peripheral visual field, even though the center of the fixation cross itself was not visible to any of the participants (i.e., it fell within the scotoma)”, a demanding task that probably explains the reduced number of trials that patients were able to complete during each session. Rosengarth et al (2013) trained AMD patients using an oculomotor task, reporting improvements in reading speed (10 words/min) and fixation stability (30%).…”
Section: Perceptual Learning In Amdmentioning
confidence: 99%
“…However, the main limitations of this study are the absence of a control group (although authors used a test-retest sample of five patients, finding no changes in the measured visual abilities) and the lack of monitoring of the PRL position during training. Astle et al (2015) trained AMD patients in a word identification task and reported a significant improvement in reading speed and baseline performances. Improvements were correlated with age with younger participants performing better than the elderly.…”
Section: Perceptual Learning In Amdmentioning
confidence: 99%